2010
DOI: 10.1534/genetics.110.114769
|View full text |Cite
|
Sign up to set email alerts
|

Transformation/Transcription Domain-Associated Protein (TRRAP)-Mediated Regulation of Wee1

Abstract: The G2 DNA damage checkpoint inhibits Cdc2 and mitotic entry through the dual regulation of Wee1 and Cdc25 by the Chk1 effector kinase. Upregulation of Chk1 by mutation or overexpression bypasses the requirement for upstream regulators or DNA damage to promote a G2 cell cycle arrest. We screened in fission yeast for mutations that rendered cells resistant to overexpressed chk1 1 . We identified a mutation in tra1, which encodes one of two homologs of transformation/transcription domain-associated protein (TRRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 78 publications
3
14
0
Order By: Relevance
“…This sensitivity is in concordance with the DNA microarray analysis, which revealed that changes in the gene expression pattern upon the adaptation of eca39⌬ are negatively correlated with those observed in a tra1 mutant ( Fig. 2C; supplemental Table 3) (26). The involvement of spt8 ϩ and tra1 ϩ suggests that NH 4 Cl resistance is under the control of the whole SAGA complex, although smaller complexes such as the Ada2-Ada3-Gcn5 complex or Gcn5 alone have also been described (27).…”
Section: Deletion Of the Saga Hat Module Subunit In A Leucine Auxotrosupporting
confidence: 86%
See 1 more Smart Citation
“…This sensitivity is in concordance with the DNA microarray analysis, which revealed that changes in the gene expression pattern upon the adaptation of eca39⌬ are negatively correlated with those observed in a tra1 mutant ( Fig. 2C; supplemental Table 3) (26). The involvement of spt8 ϩ and tra1 ϩ suggests that NH 4 Cl resistance is under the control of the whole SAGA complex, although smaller complexes such as the Ada2-Ada3-Gcn5 complex or Gcn5 alone have also been described (27).…”
Section: Deletion Of the Saga Hat Module Subunit In A Leucine Auxotrosupporting
confidence: 86%
“…2C; supplemental Table 3) (13,15,23,25,26). In particular, the deletions of the SAGA HAT module subunits, including ada2 ϩ and ada3 ϩ (12, 27) as well as the catalytic subunit gcn5 ϩ , were most highly correlated.…”
Section: The Eca39⌬ Mutant Exhibits An Adaptive Growth Phenotype On Mmentioning
confidence: 96%
“…Samples were taken at appropriate intervals for the described assays. DNA content was determined with a FACS Caliber (Becton Dickinson) as described previously (Calonge et al, 2010). Mutation rates in can1 were calculated using the method of the median from 11 independent cultures as previously described (Lee et al, 2007).…”
Section: General 975hmentioning
confidence: 99%
“…All other assays were performed on cells grown in minimal medium (EMM2). General methods for microscopy, transformation, Western blotting, and drug and radiation sensitivities were as described previously (17,(29)(30)(31). DNA was stained with 1 g/ml 4=,6-diamino-2-phenylindole (DAPI).…”
Section: Methodsmentioning
confidence: 99%